Factors Influencing Indonesian Students' Performance on PISA 2018 - M. Mujiya Ulkhaq (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Education plays a pivotal role in national development, and assessing its quality is crucial. One widely recognized international assessment is the OECD's PISA, which evaluates mathematics, science, and reading abilities among 15-year-old students globally. In 2018, Indonesian students scored below the OECD average, highlighting deficiencies in the education system. This study investigates the determinants influencing Indonesian students' PISA scores using 2018 data. Multiple linear regression is employed to analyze three models: mathematics, science, and reading scores as dependent variables. Independent variables include age, gender, study time in mathematics, science, and reading, economic, social, and cultural status, family wealth, home ICT ownership, teacher feedback, and school discrimination perception. The findings reveal varying influences on PISA scores across domains: age does not affect mathematics scores, gender does not affect science scores, and all variables significantly impact reading ability scores at the 5% confidence level.